(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this project is to acquire the remote electrical parameters like voltage, current and frequency and send these real time values over network along with temperature at power station. This project is also designed to protect the electrical circuitry by operating a relay. This relay gets activated whenever the electrical parameters exceed the predefined values. This system can automatically update the real time electrical parameters continuously this system can be designed to send alerts whenever the relay trips or whenever the voltage or current exceeds the predefined limits. This project makes use of a microcontroller, as this is a prototype of the proposed project, for demonstration purpose we have used Arduino Uno here. The controller can efficiently communicate with the different sensors being used.